Synthesis of novel trichloromethyl substituted azolo[1,3,5]triazines - Kalinin, D.; Kalinina, S.; Dolzhenko, Anton (The Japan Institute of Heterocyclic Chemistry, 2012)
The triazine ring bearing a trichloromethyl group was annelated to various aminoazoles using a new effective synthetic procedure. The method of preparation involved initial formation of trichloroacetamidines in the reaction of aminoazoles with trichloroacetonitrile followed by the triazine ring closure with triethyl orthoformate affording therefore the titled compounds.